Analysis of Heat Transfer on the Effect from Mineral Crust in Evaporator Semi-Kestner Quintuple Effect - Rahadianto Wahyu Triaji; Eka Sri Yusmartini Yusmartini; Mardwita Mardwita (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
Indonesia as a large population country has the potential to become one of the largest consumers of sugar in the world. Indonesia's national sugar needs amounted to 3.2 million tons per year while domestic production was around 2 million tons. In the sugar industry, the benefits of evaporator tools are to thicken clear juice whose dissolved solid number is 7 - 11 oBrix into a thickened syrup with a dissolved solid of 55 - 60 oBrix, this process occurs through the process of evaporation of water content contained in the material. In one sugar factory, the type of evaporator used is a Semi-Kestner Evaporator with the quintuple effect principle. One of the biggest challenges of evaporators is the decrease in heat value of the evaporator due to the onset of mineral crust that inhibits heat transfer. On September 7th, 2021 Q evaporator 1 is at 135874.8 Kw and on October 26th, 2021 Q evaporator 1 is at 121399.2 Kw. Based on the results of data observations on the evaporator carried out in September 2021 and October 2021, it can be concluded that the decreased heat transfer will cause the evaporator's performance in evaporating water from the sap material (clean juice) so that the material flow rate is getting bigger. Efforts that can be made to overcome this are to carry out mechanical cleaning or chemical cleaning per 28 days of the grinding process, to remove crusts on the tube calandria evaporator.